Synergistic effects of yoga and ayurvedic nutrition on middle-distance running performance: A randomized clinical trial - Ashish Kumar Mishra; Aakanksha Heer; Medha Kulkarni; Tanuja M Nesari; Man Singh (Yoga-Mimamsa, 2025)
Introduction: Yoga is known for its benefits on physical and mental well-being, while Ayurvedic diets, like those including Ragi and Urad Laddu, aim to optimize energy and recovery. Despite extensive research on sports nutrition, few studies have examined the combined effects of yoga and Ayurveda on performance. This study investigates how yoga and Ayurvedic nutrition can synergistically enhance athletic performance by improving flexibility, strength, and recovery. Materials and Methods: Ninety male athletes were randomly assigned to three groups. Group A (n = 30) was the control group. Group B (n = 30) participated in daily 1h yoga sessions, which included asanas, pranayama, and meditation. Group C (n = 30) participated in a yoga session and consumed Ragi Urad Laddu 50 g/day for 90 days. The control group did not receive any intervention. Serum protein, calcium and physical assessment were done at baseline and after completion of the study. Results: At the end of 90 days, Group B and Group C showed significant improvement in flexibility (p < 0.001), endurance (p < 0.005), agility (p < 0.001), balance (p < 0.001), and strength (p < 0.001), compared to the control group, along with a significant increase in serum calcium levels. Agni (digestive fire) (p < 0.001) improved notably in both Groups B and C. Conclusion: This study highlights the impact of yoga and Ragi Urad Laddu, suggesting that this combined approach can improve physical strength and digestive health in athletes.